Phylogenetic placement of a new Melanophilharmostes Paulian, 1968 pill scarab (Coleoptera: Hybosoridae: Ceratocanthinae) from Cameroon: molecular results decipher misleading morphology - Grebennikov, Vasily V. (Zootaxa, 2022)
This study targets two specimens of a morphologically highly unusual pill scarab from Cameroon. The original morphology-inspired hypothesis that these beetles represent a new genus is refuted. Instead, a phylogenetic analysis of 90 terminals and 3231 aligned DNA positions linked both specimens with the Afrotropical genus Melanophilharmostes Paulian, 1968. Both Cameroonian specimens are herein described as Melanophilharmostes tuber Grebennikov, new species. Re-evaluation of the morphological characters of this species in light of molecular results corroborated this taxonomic decision by detecting all three morphological autapomorphies of the genus: the presence of setae and horseshoe-shaped microsculpture on the dorsal body surface, as well as the presence of the lateral carina on each elytron. Except for a single representative of the genus Melanophilharmostes placed within the genus Pseudopterorthochaetes Paulian, 1977 (interpreted as an analytical artifact), both genera are sister groups, in agreement with the pre-existing morphology-based hypothesis. Both genera, together with the Malagasy/Comorian genus Synarmostes Germar, 1843 and monotypic Balleriodes Grebennikov, 2021 from Tanzania, constitute the strongly supported Synarmostes group of genera.